School cooperative societies in Malaysia: The inconspicuous and unique retail format with promising potentials - Ong, L.D.; Tay, A. (2011)

(untitled)
Whenever individuals discuss about the dynamics of retail businesses in Malaysia, very few would include the activities and economic contributions of the school cooperative societies. This inconspicuous but unique retail format has been in existence for decades in the country. The school cooperatives have since grown exponentially in terms of numbers, memberships, profits, and activities. Currently, there are over 2,136 of such societies and they are one of most popular co-curricular activities amongst secondary school students in Malaysia. Together they have accumulated a total of nearly RM19 million in paid up capital and assets worth more than RM200 million (Utusan Online, 2011). Young secondary students, between 13 and 17 years of age, are members and shareholders of these self-reliant and democratic retail societies. Most of them actively participate and support these, “by the people and for the people” cooperative societies for mutual benefits. While some of the more senior students with leadership potentials are nominated to be the board members of their school cooperatives, the rest become committee or ordinary members who either assist in selling or buying stationery and books from their respective small but convenient retail outlets within the premises of their schools.